Assembling Ultrasmall Copper‐Doped Ruthenium Oxide Nanocrystals into Hollow Porous Polyhedra: Highly Robust Electrocatalysts for Oxygen Evolution in Acidic Media. Issue 29 (5th June 2018) - Su, Jianwei; Ge, Ruixiang; Jiang, Kemin; Dong, Yan; Hao, Fei; Tian, Ziqi; Chen, Guoxin; Chen, Liang
Abstract: Here, a facile and novel strategy for the preparation of Cu‐doped RuO2 hollow porous polyhedra composed of ultrasmall nanocrystals through one‐step annealing of a Ru‐exchanged Cu‐BTC derivative is reported. Owing to the optimized surface configuration and altered electronic structure, the prepared catalyst displays a remarkable oxygen evolution reaction (OER) performance with low overpotential of 188 mV at 10 mA cm −2 in acidic electrolyte, an ultralow Tafel slope of 43.96 mV dec −1, and excellent stability in durability testing for 10 000 cycles, and continuous testing of 8 h at a current density of 10 mA cm −2 . Density functional theory calculations reveal that the highly unsaturated Ru sites on the high‐index facets can be oxidized gradually and reduce the energy barrier of rate‐determining steps. On the other hand, the Cu dopants can alter the electronic structures so as to further improve the intrinsic OER activity. Abstract : Cu‐doped RuO2 hollow porous polyhedra composed of ultrasmall nanocrystals are successfully synthesized as a highly active electrocatalyst toward the oxygen evolution reaction in an acidic electrolyte. The electrocatalysis activity of RuO2 is significantly improved by engineering the surface configuration and tailoring the electronic structure by means of shrinking the nanocrystal size and Cu doping, respectively.